Cognitive Modeling of Management Strategies of the Enterprises: the Experience of Developing and Testing - Karayev, Robert; Safarly, Islam I.; Abduragimov, Teymur F.; Aliyev, Kamran A. (Archives of Business Research, 2014)
The paper discusses the difficulties of choice strategies of enterprises development in modern complicated turbulent environments. Ill-structured (by G. Simon ) and the dynamic nature of the problem of choice restricts the opportunities to use traditional widely known DSS-tools (SWOT & PEST, BSC, CCB, SODA, SAM, SAST, SCA, BCG, GE / McKinsey, Shell / DPM, MD ASQ et al.). New prospects for solution of the issue open ideas and methods such us "cognitive modeling" which today is major component of the global trend of world science - «NBIC Convergence". Some progress in terms of development and use of cognitive DSS-tools of strategic management was achieved over the past two decades. However it becomes apparent (and some "bottlenecks" are caused by complex phenomenology of modern management), that it is difficult to formalize. The paper presents the methodology of cognitive modeling and cognitive DSS-tools oriented to allow deal with this kind of "bottlenecks". The purpose of the article: a) present the short overview of the main provisions and basic tools of the developed methodology, and b) present the main results obtained in process of development and testing research prototypes of cognitive models for three companies with different structure and dynamics of their macroeconomic environment. Keywords: enterprise strategy, dynamic analysis, cognitive approaches, cognitive models.